Anxiety and depression symptoms in patients with tinnitus: systematic review (Research, Society and Development, 2022)
Objective: to compare tinnitus sufferers to non-sufferers, regarding the presence of symptoms of anxiety and depression. Methodology: PubMed and Lilacs databases were searched for cross-sectional, cohort or case-control studies, with adult humans. The studies have been selected through a two-step process (title/abstract screening and full text reading). The study selection, data extraction and assessment of study quality were made independently by two reviewers. Results: 29 studies were included, totalizing 1,208,435 participants. 78% and 76% of the studies found a significant (p < 0,05) positive association between tinnitus and depression and anxiety, respectively. All the studies that compared the non-annoying tinnitus subgroup to controls found a significant (p < 0,05) positive association between non-annoying tinnitus and depression. All the studies that assessed the correlation between tinnitus-related annoyance and anxiety or depression levels found a significant (p < 0,05) positive correlation. Conclusion: tinnitus sufferers have greater odds of anxiety and depression symptoms than non-sufferers, and such finding is independent of hearing loss. The more annoying the tinnitus, the greater the prevalence and severity of the negative emotional symptoms; however, even not annoying tinnitus is associated with greater odds of depression.